Peran Manusia di Bumi Sebagai Khalifah Dalam Perubahan Sosial - Furqon, Furqon (An Naba, 2021)
In this study will be further discussed how the role of man as a caliph on the face of the earth in social change. The formulation of problems in this study is; 1) what is the role of man as caliph on earth?; 2) What is the role of man on earth as a caliph in social change? The purpose of this study is; 1) to know the role of man as caliph on earth; 2) man as caliph in social change. This study uses qualitative descriptive research type with type of literature study research. Literature research is done through books, magazines, journals, the internet and so on. In addition, by conducting observational studies from previous studies. The results found are; 1) that social changes made by the hands of man himself are often involved with matters of destiny, such as social change in society is the economic condition of society. Our duty as caliphs or human beings on earth is to improve the standard of living of the people through social change using the medium of da'wah tools. 2) man is the caliph on the earth, the duty of the caliph in the Qur'an is commonly called imaratul ardh (prospering the earth) and worship allah (worship allah). God created man from this earth and assigned man to imarah on the earth by managing and maintaining it.